The Potential of Functional Cookies Based on Ambon Bananas, Mung Beans, and Dates as a Nutritious Snack for Child Athletes: A Review Article - Anggraeta Ayu Fernanda; Arya Ulilalbab; Diana Nurrohima (Ficco Public Health Journal, 2025)
Background: Child athletes have higher energy and nutrient needs than children in general, so they require nutritious snacks that can support performance and growth. Functional cookies are a suitable alternative because they are easy to consume and practical, and can be formulated with nutritious local ingredients such as Ambon bananas, mung beans, and dates. Methods: The study was conducted through a literature review of national and international scientific journals published between 2016 – 2024, using the keywords “functional cookies”, “banana flour”, “mung bean protein”, “dates nutritional value”, and “athlete children nutrition”. Results: Ambon bananas serve as a source of complex carbohydrates and potassium, which help maintain electrolyte balance and muscle function; mung beans contribute to increased vegetable protein and fiber intake with a low allergy risk; and dates, particularly the Sukari variety, provide quick energy and natural antioxidants that support the immune system. Several studies have shown that this combination of ingredients produces cookies with high energy, protein, and mineral content, as well as good organoleptic acceptance. Conclusion: Functional cookies made with Ambon bananas, mung beans, and dates have the potential to be a nutritious, functional snack that children will love and can support optimal health, growth, and performance in children's athletes.